2008
DOI: 10.1177/0267659109105254
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after coronary artery bypass surgery with miniaturized versus conventional cardiopulmonary bypass

Abstract: We have reviewed the results of our experience with the use of miniaturized (Mini-CPB) versus conventional (C-CPB) cardiopulmonary bypass in coronary artery bypass surgery (CABG). This study included 365 patients who underwent CABG with C-CPB and 101 patients with Mini-CPB. In-hospital mortality was lower in the C-CPB group (1.4% vs. 3.0%, P = 0.38). A better, but not statistically significant, immediate outcome was observed in the C-CPB group as indicated by a shorter length of stay in the intensive care unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…This hemodilution potentially affects hemostasis, decreasing levels of coagulation and fibrinolytic proteins [15]. Additionally, the risk of long-term morbidity and short-term mortality is increased by hemodilution [29]. Increased blood transfusion is often required due to excessive hemodilution [30] to provide adequate oxygen delivery to the vital organs [2].…”
Section: Deleterious Effects Of Ccpbmentioning
confidence: 99%
“…This hemodilution potentially affects hemostasis, decreasing levels of coagulation and fibrinolytic proteins [15]. Additionally, the risk of long-term morbidity and short-term mortality is increased by hemodilution [29]. Increased blood transfusion is often required due to excessive hemodilution [30] to provide adequate oxygen delivery to the vital organs [2].…”
Section: Deleterious Effects Of Ccpbmentioning
confidence: 99%
“…In a propensity score matched group, Rimpilainen et al found that the efficacy of M-CPB was more pronounced the more complex the cardiac surgical procedure that necessitated longer perfusion times [7]. This is similar to large analyses that demonstrate that the benefit in OPCAB is in high risk patients [25].…”
Section: Common Features To M-cpbmentioning
confidence: 78%
“…Using a lower priming volume has been shown to reduce transfusions by about 30% [6]. Finally, hemodilution has been implicated as a major factor in organ dysfunction, short-term mortality, and long-term morbidity [7].…”
Section: Common Features To M-cpbmentioning
confidence: 99%
“…As such, among the aims of the mECC system are a reduction in haemodilution, post-bypass coagulopathy and the inflammatory response to bypass. Recent publications have suggested that, to a certain extent, this has been achieved, associating mECC with a reduction in inflammation, haemodilution, post-operative blood transfusion requirements and stroke rates when compared to traditional CECC 10-12 . No short-term difference in morbidity or mortality has been shown between mECC and CECC, and long-term data is yet to be established.…”
Section: What Are the Benefits Of Mecc?mentioning
confidence: 99%